The effects of membrane filters used in biopharmaceutical processes on the concentration and composition of polysorbate 20. (23rd October 2013) - Lei, Ming; Hewitt, Daniel; Cornell, Christopher; Skidmore, Ken; Kao, Yung‐Hsiang; Sugahara, Jimmy; Beane, Diane; Ji, Junyan
<x xml:space="preserve">Abstract</x> Polysorbate 20 (PS‐20) is often included in the formulation for therapeutic proteins to reduce protein aggregation and surface adsorption. During the production process of therapeutic proteins, various membrane filters are used to filter product pools containing PS‐20. The purpose of this study is to quantify the effects of these membrane filtration processes on the concentration and composition of PS‐20. A quantitative understanding of this process provides the knowledge base for better controlling the consistency of formulation excipients in drug products. PS‐20 solutions (without protein) were filtered through either 0.2 µm sterilizing filters or membrane filters with 30 kDa MWCO. The concentration of PS‐20 was measured by a mixed‐mode chromatography method and a nuclear magnetic resonance spectroscopy (NMR) assay. The composition of PS‐20 was characterized by 1H‐NMR and a reverse‐phase chromatography method. Non‐specific adsorption of PS‐20 on both the sterilizing filter and 30 kDa MWCO membrane filter was quantified. Composition of PS‐20 was altered after 30 kDa MWCO membrane filtration, possibly because the different interactions between heterogeneous PS‐20 components and the 30 kDa MWCO membrane were not uniform. As a result, the retentate after the 30 kDa MWCO membrane filtration step contains no POE sorbitan and increased amount of POE sorbitan di‐esters and tri‐esters. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:1503–1511, 2013